Identifying fibroblast-derived sFRP2 as a therapeutic target and engineering siRNA therapy for uterine scarring - Juan Cheng; Siqi Zhang; Qian Gui; Zedan Pu; Zhiyu Chen; Quanfang Wei; Hongbo Qi; Jianxiang Zhang (Nature Communications)
Abstract Uterine scarring is a common complication following uterine injury, characterized by abnormal wound healing in the endometrial or myometrial tissue. However, the underlying mechanisms contributing to scar formation remain unclear, impeding the development of effective drugs for uterine scarring. Here, we identify that secreted frizzled-related protein 2 (sFRP2) is highly expressed in human and mouse uterine tissues with uterine scarring, particularly in uterine fibroblasts. Using female mouse models, we demonstrate that sFRP2 overexpression in the healthy uterus induces uterine scarring features and exacerbates surgery-induced fibrosis, while sFRP2 knockdown inhibits uterine scarring development and fibrotic transformation in uterine fibroblasts, highlighting the pivotal role of sFRP2 as an initiating driver in uterine scarring pathogenesis. Mechanistically, sFRP2 promotes uterine scar formation by activating the non-canonical Wnt signaling pathway and calcium influx in uterine fibroblasts. Additionally, therapeutic potential of targeting sFRP2 is demonstrated by developing siRNA against sFRP2 and engineering a lipid nanoparticle delivery system. The siRNA therapy effectively suppresses sFRP2 expression, reduces uterine scar formation, and improves pregnancy outcomes in female mice, underscoring the therapeutic potential of sFRP2 as a promising target for the prophylactic treatment of uterine scarring.